EPISTEMOLOGI AL-FARABI: GAGASANNYA TENTANG DAYA-DAYA MANUSIA - Hafid, Hafid (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
The philosophy of al-Farabi is a review and commentary on the philosophical works written by Greek Philosophers. Al- Farabi’s thought exposes new nuance that is brought to the tradition of Islamic treasure. Al-Farabi carries both philosophy and religion discourses, primarily in matching the philosophy of language to the religion that was polarized into language terminologies. Religion is viewed as expression of philosophical truth in the popular language that uses art, logic, rhetoric, and poetry. Al-Farabi put rhetoric and poetry into the integral-part of philosophy. Poetry has ability in creating imagination (khayali) as a description of empirical data. The power of imagination is put into logic. This is an unusual construction of logic. By the power of imagination, al-Farabi confirmed the prophetic truth. Prophet is not only the owner of intellectual capability as philosopher has, but he has the high power of imagination; prophet is capable to formulate concrete formulation from abstract conceptions that is easily understood and accepted by society and his followers.